Gender gap in pension savings: evidence from Peru’s individual capitalization system - Olivera, Javier (2022)
We study the gender gap in the accumulation of pension funds in Peru, a country where the main pension system is based on individual retirement accounts. We exploit randomly selected samples of administrative pension fund registers collected between 2005 and 2019 and find a gender gap in favour of men at each percentile of the distribution of pension funds. The unconditional gender gap decreases along the percentiles until it reaches a sort of “glass ceiling” around the 85th percentile, and then it increases substantially. We also detect heterogeneity by birth cohorts, indicating that older cohorts show higher gender gaps in pension saving because of the capitalization process. Moreover, we find that awareness about pension fund risk management –a proxy for financial literacy– increases the dispersion of pension savings over the distribution and, therefore, increases inequality. This situation is aggravated by the fact that Peru has very low levels of financial literacy.